The culture of inquisition in medieval England - Flannery, Mary C. (Mary Colleen); Walter, Katie L., 1980- (Westfield medieval studies, 2013)
Inquisition in medieval and early modern England has typically been the subject of historical rather than cultural investigation, and focussed on heresy. Here, however, inquisition is revealed as playing a broader role in medieval English culture, not only in relation to sanctions like excommunication, penance and confession, but also in the fields of exemplarity, rhetoric and poetry.